Elevated Serum Level of Krebs von den Lungen-6 Predicts Death in Patients With Comorbid Idiopathic Pulmonary Fibrosis and Obstructive Sleep Apnea - Li F; Geng J; Zhang H; Xie B; Zhang H; Xie J; Dai H (Nature and Science of Sleep)
Fei Li,1,2 Jing Geng,2 Hehe Zhang,1,3 Bingbing Xie,2 Hui Zhang,2 Jiang Xie,1,3 Huaping Dai2 1Department of Pulmonary and Critical Care Medicine, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China; 2National Center for Respiratory Medicine, State Key Laboratory of Respiratory Health and Multimorbidity, National Clinical Research Center for Respiratory Diseases, Institute of Respiratory Medicine, Chinese Academy of Medical Sciences, Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China; 3Beijing Anzhen Hospital Centre for Sleep Medicine and Science, Capital Medical University, Beijing, 100029, People’s Republic of ChinaCorrespondence: Jiang Xie, Department of Pulmonary and Critical Care Medicine of Beijing Anzhen Hospital, Capital Medical University, 2# Anzhen Road, Beijing, 100029, People’s Republic of China, Email frank782008@aliyun.com Huaping Dai, Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, Capital Medical University, 2# Yinghuayuan East Street, Beijing, 100029, People’s Republic of China, Email daihuaping@ccmu.edu.cnBackground: Obstructive sleep apnea (OSA) is prevalent in patients with idiopathic pulmonary fibrosis (IPF). This study evaluated the prognostic significance of Krebs von den Lungen-6 (KL-6) levels in patients with comorbid OSA and IPF.Methods: This retrospective research included 115 individuals diagnosed with IPF between January 2015 and December 2020, all of whom completed sleep tests and underwent measurement of serum KL-6 levels during hospitalization. To ascertain the risk factors associated with all-cause death, a multivariate Cox regression model was employed, adjusted for confounding variables of age, sex, and pulmonary function.Results: During the 40-month follow-up, 24 (20.9%) deaths occurred, with 17 (28.8%) in the OSA group and 7 (12.5%) in the non-OSA group. Patients with OSA had higher baseline KL-6 levels than did those without OSA. Both apnea-hypopnea index (hazard ratio [HR] = 1.023, 95% confidence interval [CI] 1.000– 1.047, p = 0.049) and serum KL-6 levels (HR = 1.001, 95% CI 0.999– 1.002, p = 0.032) were identified as independent risk factors for death in multivariable Cox analysis. For the overall cohort of patients with IPF, those with a KL-6 levels ≥ 1200 U/mL had a higher risk of death in both univariate analysis (HR = 5.694, 95% CI 1.945– 16.669, p = 0.002) and adjusted models (HR = 5.245, 95% CI 1.775– 15.494, p = 0.003). In the subgroup analysis, the independent prognostic significance of KL-6 levels ≥ 1200 U/mL for death was evident only in IPF patients with concurrent OSA (HR = 4.887, 95% CI 1.082– 22.067, p = 0.039), whereas it was not observed yet in IPF patients without OSA (HR = 4.652, 95% CI 0.616– 35.131, p = 0.136).Conclusion: KL-6 level is of prognostic value in patients with comorbid IPF and OSA. These findings underscore the need for sleep tests and KL-6 measurement for IPF patients at high risk.Keywords: death, idiopathic pulmonary fibrosis, obstructive sleep apnea, serum Krebs von den Lungen-6